Tuberculosis a globalized disease: Review - Nyarko, Richard Owusu; Prakash, Amit; Kumar, Nayan; Saha, Purabi; Kumar, Roshan (Asian Journal of Pharmaceutical Research and Development, 2021)
One of the deadliest infectious diseases in the world that causes millions of deaths per year is tuberculosis (TB). In this document we present an overview of TB including pathogenesis, diagnosis and recommendations for treatment. We searched PubMed for related articles on TB in preparation for this post. We have also checked for similar reporting and clinical recommendations on the websites of international organisations such as the World Health Organization and the United States Centers for Disease Control and Prevention (CDC). The aim of this paper was to give health staff, policy-makers, patients and the public general education.